Нововиявлені документи про антирадянське підпілля міста Глухова 1938 року - Степенькін, С.Ю. (Сіверщина в історії України, 2024)
У статті показано нововиявленні дані про повстанську організацію у місті Глухові. Вказано, що вона діяла у 1937–1938 роках. Її очолював Іван Дадаков. Ця організація була викрита радянськими репресивно-каральними органами. Дадакова і ще одного члена організації, Григорія Краснощока, було страчено. The article shows newly discovered data about the insurgent organization in the town of Hlukhiv. It is stated that it operated in 1937–1938. It was headed by Ivan Dadakov. This organization was formed by the detachment to fight against Soviet rule. At least 6 people were gathered. The organization was headed by Ivan Dadakov. The insurgent organization in the town of Hlukhiv was exposed by the Soviet repressive and punitive authorities. Dadakov and another member of the organization, Krasnoshchok Hryhoriy, were executed. The fate of its other members is unknown.